Study of the Use of Permethrin 5% Cream in Galicia (Spain) between 2018 and 2021 - Severo Vázquez-Prieto; Antonio Vaamonde; Esperanza Paniagua (MDPI AG, 2023)
Drug utilization studies can provide direct insights into how a drug is used in real-world conditions and can give a rough estimate of the proportion of the study population treated with it. In the present work, we examined the consumption of permethrin 5% cream in the four provinces of Galicia (a Spanish autonomous community) and described the seasonal variability and the annual evolution of its consumption between 2018 and 2021. A descriptive, cross-sectional, and retrospective study of the consumption of this drug, expressed in defined daily dose per 1000 inhabitants per day (DID), was carried out. The results obtained revealed differences between the amounts consumed in the four Galician provinces (p < 0.001). No specific geographical pattern was observed; however, the results suggested a marked seasonality and a slightly increasing global trend in the consumption of permethrin 5% cream throughout the study period. Since the only authorized indication of this drug in the study area is the treatment of scabies, this work may give an idea of the epidemiological situation of the disease in Galicia and serve to establish public health strategies against this parasitosis.